Macro- and microvascular endothelial dysfunction modulation by VCAM1 haplotypes of pediatric sickle cell anemia patients - Silva, Marisa (2020)
Sickle cell anemia (SCA) is a multifactorial-like monogenic disease that results from homozygosity for the HBB:c.20A>T mutation. Children with SCA usually present a systemic vascular disease with profound effects in organs like the brain, with stroke being the most severe end of the cerebral vasculopathy spectrum. Endothelial dysfunction plays a major role in vasculopathy and several adhesion molecules, such as vascular cell adhesion molecule 1 (VCAM-1), are produced by a cytokine-activated endothelium. In previous genotype/phenotype association studies, we found positive associations of specific VCAM1 gene promoter variants and haplotypes to high blood flow velocities in the median cerebral artery, and to chronic hemolysis biochemical markers. Our aims in this study were to: (i) assess the role of those variants, together with imaging, serological and hematological parameters as potential biomarkers of cerebral vasculopathy in SCA children, and (ii) evaluate the functional effects of the VCAM1 promoter haplotypes on endothelial cell response following endothelial activation by TNF-alpha stimulation. We investigated seventy children with SCA of sub-Saharan ancestry, with focussing on cerebral vasculopathy, as well as on stroke risk (as measured by transcranial Doppler ultrasound). PCR and Sanger sequencing were used for genotyping VCAM-1 gene. Statistical analyses were performed using SPSS (v.25.0) software. When statistical significance was identified for specific haplotypes, plasmid constructs were created by molecular cloning using a promoterless pGL4.10[luc2] vector. Haplotype sequence of each construct was confirmed by Sanger sequencing prior to transfection to EAhy926 and HBEC (macrovascular and microvascular endothelial cell models, respectively) with and without TNF-alpha stimulation. Differences in promoter activity were then assessed by luciferase reporter assays. We analysed 6 VCAM1 promoter variants and 7 haplotypes with potential modulating effect. The rs1409419_T allele and haplotype 7 (Hap7) were positively associated with stroke, stroke risk, and high levels of LDH. On the other hand, haplotype 1 (Hap1) was negatively associated with stroke. Luciferase reporter assays showed differences in promoter activity, in both endothelial cell models, as a result of Hap1 and Hap7 transfection. Hap1 endothelial cell transfection led to a decrease, while Hap7 transfection led to an increase in promoter activity. These results are consistent with: (i) lower VCAM1 expression, hence a protective effect, due to Hap1 and (ii) higher expression due to Hap7 and consequently, increased vasculopathy risk, in a pro-inflammatory milieu. The association between specific haplotypes and endothelial cell response further enhances the modifier effect of VCAM1 not only on macro- and microvascular endothelial dysfunction but also on systemic SCA vasculopathy. Furthermore, we suggest that those haplotypes, together with the imaging, biochemical and hematological parameters, may be used to design a sensitive and specific biomarker panel for SCA vasculopathy risk, severity and prognosis.